Conserved temperature requirements but contrasting responses to humidity across oviposition preferences in temperate grasshoppers - Dvořák, Tomáš; Knapp, Michal (Scientific reports, 2023)
The right choice of an oviposition site is a crucial task for oviparous species without maternal care. In contrast to well investigated biotic factors, e.g., larval food preferences, parasitism, predation, and competition avoiding, abiotic factors affecting oviposition preferences in insects have been rarely investigated in comparative studies. To improve our current understanding of oviposition site selection in Orthoptera, we investigated the influence of substrate temperature and moisture on the oviposition behaviour of 14 temperate grasshopper species. Conspecific groups of adults were kept in arenas with simultaneous temperature and moisture gradients. For each ootheca produced during the experiment (n = 1192) we recorded its depth and local microclimatic conditions. Our results indicate that microclimatic oviposition preferences significantly differ among species, however, correlations between adult habitat preferences and microclimatic oviposition preferences were surprisingly weak. Even oligothermic species preferred substrate temperatures around 30 °C and some xerothermic species preferred higher humidity. The hypothesized tendency to place oothecae closer to the ground within grass tussocks under hot and dry conditions was confirmed. It is possible that species evaluate microclimatic conditions for oviposition in the context of occupied habitat, i.e., in a relative rather than absolute manner.
Keywords: kladení vajíček; Coleoptera; brouci; Temperature; Humidity; Larva; teplota; kobylky; larva; Animals; Female; Grasshoppers; ženské pohlaví; zvířata; vlhkost; Oviposition